Democratisation and the political economy of a dysfunctional state: the case of the Democratic Republic of Congo - Kabemba, Claude Kambuya (My University, 2011)
In 2006 the Democratic Republic of Congo (DRC) organized landmark presidential and parliamentary elections after three decades of the dictatorship of President Mobutu Sese Seko and a decade of war. After three years of a difficult transition, the elections produced a legitimate government under President Joseph Kabila. Subsequently, however, the democratic dispensation has struggled to transform the DRC from a failed to a functional state. This thesis examines the causes of state failure and explores conditions that would restore statehood. The central thesis of this research is that successful state building cannot rely primarily on formal institutions such as the holding of elections, but must be linked to nation-building and building of democracy from below. Empirically the thesis looks at the development of statehood in the DRC from the pre-colonial to contemporary period. In this respect, it analyses the historical trajectories that have shaped the development of the state over the course of decades and identifies attempts to break the impasse around reforms. This thesis contributes to the existing literature on state failure in the DRC by showing how past and present conditions and circumstances are intertwined and impact on the course of state building. It argues that while the origins of state failure are located in Belgian colonization, internal Congolese weaknesses have maintained and reproduced state failure. Furthermore, the thesis proposes that although external actors, interests, and policies continue to determine political and economic dynamics in the DRC, the main challenges revolve around resolving the internal contradictions characterized by democratization without state consolidation. In addition to bad governance, the thesis considers the various strains facing the Congolese state such as the continued conflicts over resources that are fuelled by regional and international actors in collusion with local actors. The thesis concludes that external efforts to build democracy are unlikely to succeed unless there are parallel attempts to reconcile state building with nation building in the DRC